A CRITICAL ANALYSIS OF TEACHER STRATEGIES FOR DEVELOPING NOBLE MORALS IN STUDENTS WHO ACTIVELY USE SOCIAL MEDIA - Febriyanti; Ana Andriani; Y. Suyitno; Wakhudin (SOSIOEDUKASI, 2025)
Character education in the digital era presents challenges for teachers in instilling noble moral values ​​in students who actively use social media. This study aims to describe teacher strategies in developing noble morals in elementary school students who actively use social media in one of the clusters in Maos, Cilacap. The research method is descriptive qualitative with a case study method. The research subjects include teachers, students, and school principals. Research data were collected through observation, interviews, and documentation, then analyzed using the Miles, Huberman, and Saldana model, which includes data condensation, data presentation, and drawing conclusions. Data validity uses technical triangulation and source triangulation. The results of the study show that teachers apply four main strategies in instilling noble morals in students who actively use social media, namely habituation, role modeling, reflection, and management of digital interactions. The five main values ​​of noble morals developed include (1) faith through prayer, congregational prayer, worship journals, and digital religious content; (2) honesty through role modeling, consequence simulation, digital literacy, and reflection on responsibility; (3) caring through real and digital social activities, sharing, helping friends, and rejecting bullying; (4) politeness through polite communication, 5S culture, and digital interaction ethics; and (5) responsibility through real roles, digital content management, discipline evaluation, and ethical reflection. This study confirms that strengthening character education requires a holistic approach, integration of digital literacy, and teacher role models, accompanied by school and parental support to instill noble morals in a sustainable manner.